Sonographic Images of Hepatic Portal Venous Gas in a Patient with Gastrointestinal Ischemia - Piotr F. Czempik; Oskar Bożek; Łukasz J. Krzych (Diagnostics, 2022)
Hepatic portal venous gas (HPVG) detected by ultrasound (US) following liver transplantation or in suppurative cholangitis was described previously. To our knowledge, there have been no descriptions of HPVG detected by US in acute mesenteric ischemia. Here we present diagnostic images of a 52-year-old female who was admitted to the intensive care unit (ICU) following successful embolization of a ruptured saccular aneurysm of the right vertebral artery. During their stay in the ICU, the patient developed hypotension with low systemic vascular resistance and hypovolemia. Based on physical examination of the abdomen and laboratory results, preliminary diagnosis of intra-abdominal sepsis was made. Early abdominal US was performed to find the source of sepsis. The preliminary diagnosis of stomach/small intestine ischemia was made by ultrasonic detection of HPVG. Other less likely diagnoses were pneumobilia due to cholangitis, hepatic micro-abscesses, and punctuate calcifications. The diagnosis was confirmed by multi-phase abdominal computed tomography. The explorative laparotomy revealed necrosis of the stomach, small intestine, and liver. Due to the severity of necrosis, surgical treatment was abandoned. Provided sonographic images show HPVG as an ominous sign of small intestine and stomach ischemia. Early liver US should be performed whenever intra-abdominal pathology is suspected.